Aroma and quality of breads baked from old and modern wheat varieties and their prediction from genomic and flour-based metabolite profiles. (March 2020) - Longin, Friedrich; Beck, Heiner; Gütler, Hermann; Heilig, Wendelin; Kleinert, Michael; Rapp, Matthias; Philipp, Norman; Erban, Alexander; Brilhaus, Dominik; Mettler-Altmann, Tabea; Stich, Benjamin
Graphical abstract: Highlights: Large differences observed for bread odor and flavor of diverse wheat varieties. Bread of old and modern wheat varieties does not differ in odor and flavor. Bread odor and flavor can be predicted using metabolite and SNP profiles. Possibilities shown to increase the wheat quality for consumers in the product chain. Abstract: Bread aroma is the principal characteristic perceived by the consumer yet it is mostly disregarded in the product chain. The main aim of this study was to evaluate the potential to include bread aroma as a new target criterion into the wheat product chain. The objectives of our study were to (i) quantify the influence of genetic versus environmental factors on the bread aroma and quality characteristics, (ii) evaluate whether bread baked from modern wheat varieties differ in terms of aroma from those baked from old varieties, and (iii) compare genomic and metabolomic approaches for their efficiency to predict bread aroma and quality characteristics in a wheat breeding program. Agronomic characters as well as bread aroma and quality traits were assessed for 18 old and 22 modern winter wheat varieties evaluated at up to three locations in Germany. Metabolite profiles of all 120 flour samples were collected using a 7200 GC-QTOF. Considerable differences in the adjusted entry means for all examined bread aroma and quality characters were observed. For aroma, which was rated on a scale from 1 to 9, the adjusted entry means varied for the 40 wheat varieties between 3 and 8. In contrast, the aroma of bread prepared from old and modern wheat varieties did not differ significantly (P < 0.05). Bread aroma was not significantly (P < 0.05) correlated with grain yield, which suggested that it is possible to select for the former character in wheat breeding programs without reducing the gain of selection for the latter. Finally, we have shown that bread aroma can be better predicted using a combination of metabolite and SNP genotyping profiles instead of the SNP genotyping profile only. In conclusion, we have illustrated possibilities to increase the quality of wheat for consumers in the product chain.